Irrigation water quality and its impact on the physicochemical and microbiological contamination of vegetables produced from market gardening: a case of the Vea Irrigation Dam, U.E.R., Ghana - Nang Biyogue Douti (IWA Publishing, 2021)
The rationale for this study was to assess the physicochemical and bacteriological qualities of the Vea irrigation water and resultant effects on the quality of fresh vegetables produced in the area and associated implications for consumers’ health. A total of 45 water samples were collected from the reservoir and canals. Also, 16 vegetable samples comprising four samples each of tomatoes, carrots, spring onions, and cabbages were collected from four farms with installed irrigation systems fed by the Vea Dam. The irrigation water samples were analyzed for total coliform (TC) and fecal coliform (FC), Escherichia coli, pH, and turbidity, while the samples of vegetables were analyzed for TC and FC, and E. coli. The results showed that except for pH, the bacterial loads and turbidity of the sampled vegetables and irrigation water were above the standards of the WHO and the International Commission on Microbiological Specifications for Food. Comparatively, the samples of cabbage recorded the highest levels of microbial contamination. The study suggests that the water should be treated before being used for irrigation; consumers should ensure that vegetables are properly washed and cooked/treated before consumption; and periodic monitoring and assessment should be done to ensure that the adverse effects of these activities are forestalled. HIGHLIGHTS Agriculture continuously competes for a limited water supply that is becoming scarcer.; The microbial quality of irrigation water is vital to the safety of fresh and minimally handled vegetables.; Pasturing around water bodies affects water quality bacteriologically.; Washing farm tools and materials and drawing water for watering crops affect water quality.; Piling dung along water body affects irrigable water through runoff.;